Preoperative risk factors of malnutrition for cardiac surgery patients - Ringaitienė, Donata; Gineitytė, Dalia; Vicka, Vaidas; Žvirblis, Tadas; Šipylaitė, Jūratė; Irnius, Algimantas; Ivaškevičius, Juozas (Acta medica Lituanica, 2016)
Background. Malnutrition (MN) is prevalent in cardiac surgery, but there are no specific preoperative risk factors of MN. The aim of this study is to assess the clinically relevant risk factors of MN for cardiac surgery patients. Materials and methods. The nutritional state of the patients was evaluated one day prior to surgery using a bioelectrical impedance analysis phase angle (PA). Two groups of patients were generated according to low PA: malnourished and well nourished. Risk factors of MN were divided into three clinically relevant groups: psychosocial and lifestyle factors, laboratory findings and disease-associated factors. Variables in each different group were entered into separate multivariate logistic regression models. Results. A total of 712 patients were included in the study. The majority of them were 65-year old men after a CABG procedure. Low PA was present in 22.9% (163) of patients. The analysis of disease-related factors of MN revealed the importance of heart functions (NYHA IV class OR: 3.073, CI95%: 1.416–6.668, p = 0.007), valve pathology (OR: 1.825, CI95%: 1.182–2.819, p = 0.007), renal insufficiency (OR: 4.091, CI95%: 1.995–8.389, p